2018
DOI: 10.21037/jtd.2018.05.76
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin versus heparin in percutaneous coronary intervention—a systematic review and meta-analysis of randomized trials stratified by adjunctive glycoprotein IIb/IIIa strategy

Abstract: Bivalirudin is associated with less major bleeding compared to heparin, regardless of GPI use. The lower anticoagulant effect of bivalirudin is linked with higher stent thrombosis and a trend towards more MI, however a confounding effect of GPI use in the heparin arm cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Anticoagulation regimen during PCI is one of the main determinants of bleeding risk. Bivalirudin was associated with less bleeding compared with heparin regardless of glycoprotein IIb/IIIa inhibitor use but at the expense of higher ST risk . In relation to access site, bivalirudin was associated with decreased bleeding risk in TF‐PCI but not when TR‐PCI was performed .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Anticoagulation regimen during PCI is one of the main determinants of bleeding risk. Bivalirudin was associated with less bleeding compared with heparin regardless of glycoprotein IIb/IIIa inhibitor use but at the expense of higher ST risk . In relation to access site, bivalirudin was associated with decreased bleeding risk in TF‐PCI but not when TR‐PCI was performed .…”
Section: Discussionmentioning
confidence: 98%
“…Bivalirudin was associated with less bleeding compared with heparin regardless of glycoprotein IIb/IIIa inhibitor use but at the expense of higher ST risk. 36 In relation to access site, bivalirudin was associated with decreased bleeding risk in TF-PCI but not when TR-PCI was performed. 37 Therefore, bivalirudin would be preferred when complex TF-PCI of LM is considered appropriate in those at high bleeding risk.…”
Section: Clinical Presentationmentioning
confidence: 94%
“…This claim was further supported by a systematic review focusing on clinical trials that compared bivalirudin to heparin from January 2000 to December 2017 in over 53,000 patients. Narayanan et al reported that bivalirudin was associated with less major bleeding complications, however, there was an increased incidence of in-stent thrombosis [17]. Although bivalirudin has this shortcoming, there is data on post-PCI agents that have favorable IST outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The latest meta-analysis published in 2018 by Anantha-Narayanan that included 22 randomized studies and four subgroup analysis with 53,364 patients compared the use of the bivalirudin to heparin, with and without adjunctive glycoprotein IIb/IIIa inhibitors (GPI) in PCI [5]. Over a mean follow-up of 192 ± 303 days, the major bleeding was lower in the bivalirudin group with (risk ratio [RR] 0.64, 95% confidence interval [CI] 0.53-0.77, p < 0.001) and without (RR 0.71, 95% CI 0.51-0.99, p = 0.041) provisional or routine use of GPIs.…”
Section: Bivalirudin In the Revascularization Of The Myocardium In Acsmentioning
confidence: 99%
“…Anticoagulant therapy is particularly important in the periprocedural period in the case of invasive treatment of acute coronary syndrome (ACS). Since the last consensus statement of the Polish expert group for Association on Cardiovascular Interventions of the Polish Cardiac Society published in 2014 [2], new circumstances have occurred that triggered the group to revise the viewpoint: 1) the new European Society of Cardiology guidelines on myocardial revascularization announced in 2018 provided indications for the use of bivalirudin in ACS; 2) new studies were published that provided essential new clinical evidence [3][4][5][6]; and 3) updated bivalirudin reimbursement code now allows for its unlimited use in myocardial infarction (MI) patients in Poland [7]. This is a 5-year update of the recommendations on the use of bivalirudin for percutaneous coronary intervention (PCI) of in ACS, tailored to the Polish healthcare setting.…”
Section: Introductionmentioning
confidence: 99%